Molecular identification of Taenia hydatigena and Mesocestoides species based on copro-DNA analysis of wild carnivores in Mongolia - Gelegbalsan Ulziijargal (International Journal for Parasitology: Parasites and Wildlife, 2020)
Cyclophyllidean tapeworms obligatorily parasitize numerous mammalian species, including herbivores, domestic animals and humans, of which, the genera Taenia and Mesocestoides are well characterized. However, little is known about these parasitic infections in wild animals. This study aims to investigate the prevalence and distribution of Taenia sp. and Mesocestoides sp. in wild carnivores in Mongolia by identifying tapeworm species based on mtDNA analysis. The field survey was carried out in 2012–2013 in 19 provinces located in different ecological regions. A total of 405 fecal samples from wild carnivores were collected. Specific DNA markers in fecal samples was detected via copro-DNA analysis and tapeworm species were identified by DNA sequencing. From 27.7% (112/405) of samples, cox1 and 12S rRNA genes of tapeworms were amplified. Further, Taenia hydatigena (50.0%, 56/112) and two Mesocestoides species, including Mesocestoides sp.-1 (36.6%, 41/112) and Mesocestoides sp.-2 (13.4%, 15/112) were identified by DNA sequencing. The prevalence of T. hydatigena was 19.9% (27/136), 13.8% (23/167), 4.8% (3/62), and 7.5% (3/40) in wolves, red foxes, corsac foxes, and snow leopards, respectively. The prevalence of Mesocestoides sp.-1 was 14.7% (20/136), 9% (15/167), 9.7% (6/62) in wolves, red foxes, and corsac foxes, while the prevalence of Mesocestoides sp.-2 was 4.4% (6/136), 1.8% (3/167), 3.2% (2/62), and 10.0% (4/40) in wolves, red foxes, corsac foxes, and snow leopards, respectively. T. hydatigena was found throughout all ecological regions, while Mesocestoides sp.-1 was in the mountain taiga, forest-steppe, steppe, desert-steppe, and desert, and Mesocestoides sp.-2 in the alpine, forest-steppe, steppe, and desert-steppe ecoregions. This study revealed the prevalence and distribution of cyclophyllidean tapeworms in wild carnivores in Mongolia; while also confirming that wolves, red foxes, corsac foxes, and snow leopards serve as definitive hosts for unidentified Mesocestoides species. Keywords: Taenia hydatigena, Mesocestoides sp., cox1 gene, 12S rRNA gene, Wild carnivores, Mongolia